Developing a platform for production of the oxylipin KODA in plants. (27th December 2021) - Ihara, Yuta; Wakamatsu, Takayuki; Yokoyama, Mineyuki; Maezawa, Daisuke; Ohta, Hiroyuki; Shimojima, Mie
Abstract: KODA (9-hydroxy-10-oxo-12( Z ), 15( Z )-octadecadienoic acid) is a plant oxylipin involved in recovery from stress. As an agrichemical, KODA helps maintain crop production under various environmental stresses. In plants, KODA is synthesized from α-linolenic acids via 9-lipoxygenase (9-LOX) and allene oxide synthase (AOS), although the amount is usually low, except in the free-floating aquatic plant Lemna paucicostata . To improve KODA biosynthetic yield in other plants such as Nicotiana benthamiana and Arabidopsis thaliana, we developed a system to overproduce KODA in vivo via ectopic expression of L. paucicostata 9-LOX and AOS. The transient expression in N. benthamiana showed that the expression of these two genes is sufficient to produce KODA in leaves. However, stable expression of 9-LOX and AOS (with consequent KODA production) in Arabidopsis plants succeeded only when the two proteins were targeted to plastids or the endoplasmic reticulum/lipid droplets. Although only small amounts of KODA could be detected in crude leaf extracts of transgenic Nicotiana or Arabidopsis plants, subsequent incubation of the extracts increased KODA abundance over time. Therefore, KODA production in transgenic plants stably expressing 9-LOX and AOS requires specific sub-cellular localization of these two enzymes and incubation of crude leaf extracts, which liberates α-linolenic acid via breakdown of endogenous lipids. Abstract : We established a system for KODA production in seed plants that takes advantage of the abundance of the substrate, α-linolenic acid, in vegetative tissues.